Rancang Bangun Sistem Remot Inframerah Air Conditioner Berbasis Internet of Things - Pratama, Bagus Gilang; Oni Yuliani; Karan Gunawan (ReTII, 2021)
The Internet of Things (IoT) is becoming increasingly popular. IoT has been used to assist people in almost every field in their daily lives. IoT is used in a variety of fields, including agriculture, animal husbandry, automotive, and others, to work more efficiently and improve performance in order to achieve the best results. Researchers used the ESP8266 as an AC controller and Home-Assistant as a web application interface to create an AC remote for monitoring and controlling AC temperature in this study. The AC remote that we created aims to make it easier for room users to control the air conditioner from anywhere, at any time, and with any device as long as they have a browser, such as Firefox or Chrome. The system we developed can adjust the air conditioner’s temperature based on the temperature settings specified by the user via the home-assistant web application. Users can adjust the temperature of their air conditioner using their smartphone or a laptop.